A proactive property management model that integrates real estate provision and facilities services management - Then, Danny Shiem‐Shin (International Journal of Strategic Property Management, 2010)
The creation of suitable workplace environment to support employees in performing their tasks is becoming a key issue for many organisations faced with constant change. Numerous workplace strategies have evolved in recent years to provide for convenience and flexibility, as well as functionality and privacy. Problems usually arise at the implementation stage where organisation culture and practices often run counter to the need for innovation strategies. This paper contents that the creation of enabling workplace requires a proactive property management model that integrate real estate provision and facilities services management. The value contribution of real estate assets can only be optimised when the property/facilities professional takes on the responsibility of continuously providing appropriate facility solutions to business challenges. An essential prerequisite is the role of property/facilities management as the custodian and enabler of the corporate workplace environment. The focus of the research was to provide a business perspective to the role of real estate assets(property) in supporting the fulfilment of corporate business plans. Based a comprehensive survey of published literature and a series of in‐depth interviews of corporate real estate/property/facilities managers, an integrating resources management framework was developed to model the nature of interactions between strategic business planning and facility operations in an organisational setting.First Published Online: 18 Oct 2010